O uso de morfometria geométrica como ferramenta no teste de diferenças entre as castas sociais em Mischocyttarus cassununga Von Ihreing (Hymenoptera, Vespidae, Polistinae) - Oliveira, Luiz Roberto de (2020)
Paper wasps (Hymenoptera, Vespidae, Polistinae) are model organisms for studies on social behavior within Insecta, as they exhibit colonial organizations and varied mechanisms of caste differentiation. Among the species of the group, Mischocyttarus cassununga von Ihering is a species that has independent nesting foundation and stable colonial hierarchy. Nevertheless, the presence of varieties with marked morphological differentiation in M. cassununga is still controversial. The present study aimed to use geometric morphometric techniques to evaluate possible differences in body structures of females of M. cassununga from different social castes. Twenty-seven nests were sampled, totaling 102 specimens, in two collection areas: the campus of the Universidade Federal de Lavras (Lavras / MG) and the rural area of Campo do Meio / MG. For the prior determination of the varieties the following criteria were considered: (i) stage of ovarian development; (ii) relative age estimated by staining of the metasomal sterna; (iii) pattern of wing wear. We obtained images of three body structures (clypeus, sternum II and wing) of each specimen, using a Canon EOS Rebel T6 digital camera coupled to a stereoscopic microscope. Anatomical landmarks were inserted in the images of each structure using Tpsutil v. 1.6 and Tpsdig v. 2.19, and these landmarks were later overlapped through the Generalized Procrust Analysis (AGP). The difference between the varieties was tested using principal component analysis (PCA), regression for correction of allometry effects, and discriminant and canonical analysis. All analyzes were performed using MorphoJ v. 2.0. The results of the statistical analyzes showed no evidence of significant results for caste separation in any of the structures analyzed. Thus, there was no morphological differentiation using geometric morphometry techniques among M. cassununga varieties, suggesting that the social castes are determined by behavioral interactions among adults.